Long-term survival of a patient with gastric cancer with bone marrow metastasis receiving S-1 plus oxaliplatin beyond three years: a case report and literature review - Suto, Hirotaka; Inui, Yumiko; Okamura, Atsuo (Frontiers in Oncology, 2024)
Background Bone marrow metastasis (BMM) of gastric cancer (GC), which is the most common cause of disseminated intravascular coagulation (DIC) among solid tumors, has a poor prognosis. Studies on prognostic improvement beyond one year in patients with GC with BMM are limited. This is the first report of a patient who survived over three years after 30 months of S-1 plus oxaliplatin (SOX) therapy for GC with BMM. Case Report The patient was a 72-year-old woman who presented with anemia and high levels of alkaline phosphatase (ALP) and carbohydrate antigen 19-9 (CA19-9). Detailed examination led to the diagnosis with BMM of GC uncomplicated by DIC and the SOX regimen was initiated in November 2018. After six cycles, she was switched to S-1 monotherapy, and both ALP and CA19-9 levels reached normal by November 2019. However, computed tomography in April 2021 showed multiple bone metastases. Therefore, she was switched to paclitaxel-based therapy. In November 2021, the patient was further switched to nivolumab monotherapy, but she succumbed due to DIC in March 2022. Conclusion GCs with BMM are prone to DIC, and the SOX regimen, which includes S-1 with efficacy against micrometastases, may constitute a safe and effective treatment modality.